Descending on the knees when prostrating - Karaliti, Bekim (Journal of Islamic Sciences, 2020)
From the matters of jurisprudence in which there is great differing of scholarly opinion is the issue of going down into prostration upon the knees or the hands. Taking into account that this matter comes up frequently, I chose to study this matter through comprative jurisprudence, by illustrating the varying opinions of the jurists, their evidences and discussions, and pointing out the reason for the difference in opinion in the matter, and mentioning the opinion I found to be most correct through my research. The reason for doing all this is to give the reader a multi-faceted view of the matter, so that they may be informed of the Islamic verdict with its evidences, and that they come to know that this is a matter where ijtihad(scholarly discretion) is allowed; to steer away from unnecessary disputes.The most important results of this study:• The differing in opinion on this issue is present from the time of the Sahabah, may Allah be pleased with them.2.The evidences in the matter are similar and proportionate.3.The most correct opinion is going into prostration upon the knees before the hands
Keywords: going down; knees; prostration